Bond of spliced GFRP reinforcement bars in alkali activated cement concrete. (15th September 2017) - Tekle, Biruk Hailu; Khennane, Amar; Kayali, Obada
Highlights: Experimental study of lap splicing of GFRP bars in alkali activated cement concrete. Numerical simulation for further study of tensile and bond stress distribution. Validation of numerical models against experimental load-deflection curves. Tensile stress distribution along the splice length changed with the load. The bond stress displayed a complex distribution along the splice length. Abstract: Glass Fibre Reinforced Polymer (GFRP) bars and Alkali Activated Cement (AAC) concrete are promising materials for replacing steel bars and ordinary Portland cement concrete. These materials can provide a solution to the associated corrosion and environmental issues. However, no design recommendations are available on splicing of GFRP bars in AAC concrete. This may be mainly due to insufficient data that would guide such recommendations. In this paper, the results of testing beams with spliced bars are presented mainly from consideration of the bond property between the spliced GFRP bars and the AAC concrete. The effects of splice length, compressive strength of concrete, and stirrup confinement on the bond behaviour are investigated. Ultimate moment capacity, failure modes, cracking pattern, and strain values in the bars have been determined and used in the analysis. A three-dimensional finite element model (FEM) was then developed. The FEM results show that the model accurately reproduces the experimental behaviour of splice tests with regard to load-deflection curves and failure modes. The reported results and numerical analysis are intended for understanding distribution of tensile and bond stresses in GFRP reinforced AAC concrete. These distributions were observed to be dependent on the applied load.